Traffic aware wireless sensor networks MAC protocol for smart grid applications using spiral backoff mechanism - Ahmed, Musse Mohamud; S. M., Sadakatul Bari; Habaebi, Mohamed Hadi; Khan, Sheroz; Anwar, Farhat (2014)
Smart grid is an innovative electrical power delivery networks which integrate distributed renewable energy sources and electric vehicles with the main power grid. Smart grid employs communication network to automate the generation, transmission and distribution and collect metering information from different parts of the grid and the customers to optimize energy distribution and consumption. Moreover, Distribution automation, Demand-Response (DR) and Direct Load Control (DLC) are applied to reduce the consumption of electricity during peak hours. However, it requires a robust, reliable communication network to facilitate real time data exchange between the utility gateway and smart meters of the customer premises. IEEE 802.15.4 standard provides a low cost, low power WSNs solution for smart grid communication networks. The IEEE 802.15.4 standard uses slotted Carrier Sense Multiple Access-Collision Avoidance (CSMA-CA) with binary exponential backoff algorithm (BEB) to avoid collision between the sensor nodes. However, BEB does not consider the s requirement which degrade the smart grid network performance. In this paper, a traffic aware spiral backoff mechanism is proposed to improve the network performance. Simulation results show that proposed spiral backoff algorithm reduces the end-to-end delay and increase packet delivery ratio (PDR) for real time data.